Efficient Oxidase Biosensors Based on Bioelectrocatalytic Surfaces of Electrodeposited Ferrocenyl Polycyclosiloxanes—Pt Nanoparticles - Alvaro Boluda; Carmen M. Casado; Beatriz Alonso; M. Pilar García Armada (Chemosensors, 2021)
The in-situ synthesis of catalytic surfaces with metallic nanoparticles must overcome the issues related to particle aggregation and polydispersity in the particle size. This work achieves it by using two electrodeposited ferrocenyl polycyclosiloxane polymers (MFPP and FPP) as templates for electro-synthesize Pt nanoparticles (PtNPS). In addition, this new electrode surface combines two efficient electrocatalysts: Ferrocene and Pt nanoparticles, with synergistic biocatalytic properties that constitute an electrocatalytic framework for the covalent immobilization of xanthine oxidase. In this work, we present the results of the kinetic, electrochemical and analytical studies of the prepared electrodes. These results showed that the PtNPs/FPP system is the best bioelectrocatalytic surface and improves other more complex xanthine oxidase devices based on the hydrogen peroxide oxidation, allowing the use of lower measuring potential with good sensitivity, wider linear ranges and low detection limits. In addition, this electrode provides the novelty of allowing the measurement of xanthine through the enzymatic consumption of oxygen at potential −0.1 V with a sensitivity of 1.10 A M−1 cm−2, linear ranges of 0.01–0.1 and 0.1–1.4 mM, low detection limit (48 nM) and long-term stability. The new device has been successfully applied to the determination of xanthine in fish meat.